(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The study aimed to evaluate the effectiveness of improving the quality of antibiotic prescribing by dentists in Ho Chi Minh Ccty before and after using HDKS and CCKS. Method: Prospective study collected data from 73 dentists working in Ho Chi Minh city using a questionnaire based on the online tool Google Form, provided attached Guidelines and antibiotic prescription self-audit tool in two phases – before and after using the Guidelines. Method: Prospective study collected data from 73 maxillofacial doctors working in Ho Chi Minh City using a questionnaire based on the online tool Google Form, provided with HDKS và CCKS at two times before and after using HDKS. Results: Among 458 antibiotic prescriptions collected in both phases, 215 were necessary (46.9%) and 243 unnecessary (53.1%). Of the 215 necessary antibiotic prescriptions, 140 were reasonable (65.1%) and 75 were unreasonable (34.9%). The rate of unnecessary antibiotic prescriptions in phase 2 (43.0%) significantly decreased compared to phase 1 (57.6%) (p < 0.05), while the rate of unreasonable antibiotic prescriptions was not significantly different between the two phases. Conclusions: Our research shows that there is still a significant proportion of unnecessary and unreasonable prescriptions in dental treatment. Preliminary results suggest that antibiotic prescribing Guidelines combined with the antibiotic prescription self-audit tool may improve appropriate antibiotic prescribing.